(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Walkability is a significant concept in sustainable urban design. Walking helps to cut ozone depleting layer and various emissions that are harmful for the environment by requiring less driving and improve occupants’ wellbeing by giving more freedom to work out decrease probability of crime by providing opportunities for social connection among people. An extensive study of literature by various scholars has been done on the relationship between natural factors and walking activity. The investigations show that the spaces designed for pedestrians those that are human-scaled, comfortable in all aspects and appropriate for people on foot could motivate people to walk, and accordingly could improve general wellbeing of people. Elements impacting walkability incorporate the presence or absence of physical condition and nature of pathways or walkways, traffic conditions, land use planning nearness of the buildings, and sense of security, among others. In particular, the investigation records various key factors affecting walkability by reviewing and summarizing the studies previously done by various scholars. Furthermore, this paper assesses walkability of two different roads of the same city - Indore Sarafa Bazaar road and Vasant Vihar road by scrutinizing all the design and planning factors that are human made. Additionally, ideas are given for improving walkability on the roads and encourage people to travel on foot. The outcomes from this exploration give knowledge into how urban designers can comprehend the collaboration between the built environment and walkability.